EFEKTIVITAS GERAKAN LITERASI DIGITAL DI SEKOLAH JENJANG PENDIDIKAN DASAR DI KOTA PONTIANAK - Ady Setiawan; Lukmanulhakim Lukmanulhakim; Andini Linarsih (Jurnal Visi Ilmu Pendidikan, 2023)
The purpose of this study was to obtain information on the effectiveness of the digital literacy movement and what factors influence the effectiveness of the digital literacy movement in Sekolah Dasar Negeri dan Sekolah Menengah Pertama Negeri Kota Pontianak. The research approach used is quantitative research and descriptive study. The data for this study were sourced from schools, especially from principals and teachers, with details as many as 141 Sekolah Dasar Negeri and 28 Sekolah Menengah Pertama Negeri. The data collection technique is direct communication by conducting interviews with principals, teachers and students. Analysis of research data using Content Input Process and Product (CIPP) analysis, then the data is analyzed using SPSS statistics program. The digital literacy movement in Pontianak State Elementary Schools and Junior High Schools in general is still not effective. Judging from the class base, school culture base, and community base. There are several factors that influence the effectiveness of the digital literacy movement in Sekolah Dasar Negeri dan Sekolah Menengah Pertama Negeri Kota Pontianak.